A comprehensive list of cloned human DNA sequences - Schmidtke, Jörg (1990)
A list of DNA sequences cloned from the human genome is presented. Intended as a guide to clone availability, this list includes published reports of cDNA, genomic and synthetic clones comprising gene and pseudogene sequences, uncharacterised DNA segments and repetitive DNA elements.